2019
DOI: 10.1177/0271678x19872563
|View full text |Cite
|
Sign up to set email alerts
|

Choroid plexus perfusion and intracranial cerebrospinal fluid changes after angiogenesis

Abstract: Recent studies have provided evidence that cortical brain ischemia may influence choroid plexus function, and such communication may be mediated by either traditional CSF circulation pathways and/or a possible glymphatic pathway. Here we investigated the hypothesis that improvements in arterial health following neoangiogenesis alter (i) intracranial CSF volume and (ii) choroid plexus perfusion in humans. CSF and tissue volume measurements were obtained from T1-weighted MRI, and cortical and choroid plexus perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 48 publications
6
26
0
Order By: Relevance
“…The choroid plexus blood flow of this work should be interpreted as apparent perfusion because of the partial volume effect in ASL images. Recent work showed consistent results between ASL and radiograph on rat brains [ 49 ], and our approach in this work was consistent with previous human studies [ 33 , 35 ]. Therefore, equivalent detectability was expected in this ASL study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The choroid plexus blood flow of this work should be interpreted as apparent perfusion because of the partial volume effect in ASL images. Recent work showed consistent results between ASL and radiograph on rat brains [ 49 ], and our approach in this work was consistent with previous human studies [ 33 , 35 ]. Therefore, equivalent detectability was expected in this ASL study.…”
Section: Discussionsupporting
confidence: 92%
“…Our study clearly demonstrated the kinetics of perfusion labeled signal and its spatial distribution. The apparent blood flow measured in this work was in agreement with Johnson et al’s ASL study [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Total blood flow of the choroid plexus showed about 38% variance, which could be from the inter-subject variation, including the choroid plexus volume variation and the average blood flow variation. Our results showed about 25% variation for either, which was consistent with the previous studies [19,30].…”
Section: Discussionsupporting
confidence: 94%
“…Our study clearly demonstrated the kinetics of perfusion labeled signal and its spatial distribution. The blood flow measured in this work was in agreement with Johnson et al's ASL study [30], although studies based on radioactive tracers and animal models reported higher blood flow. Total blood flow of the choroid plexus showed about 38% variance, which could be from the inter-subject variation, including the choroid plexus volume variation and the average blood flow variation.…”
Section: Discussionsupporting
confidence: 91%